Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Wajib Pajak Terhadap Penggunaan EFiling (Studi Empiris KPP Pratama Tanjung Karang dan KPP Pratama Kedaton Bandar Lampung) - Septi Listiawati; Kusnadi Kusnadi; Indah Lia Puspita (Universitas Malahayati, 2017)
This study aims to provide empirical evidence of influence perceived usefulness, perceivedease of use, security and privacy, Perceptions of satisfaction, Readiness of information technology hasinfluence on the use of e-Filing at Tax Office (KPP) Pratama Tanjung Karang and Tax Office (KPP)Pratama Kedaton Bandar Lampung.The population of this study are all taxpayers of priya users of efilingregistered at Tax Office (KPP) Pratama Tanjung Karang and Tax Office (KPP) PratamaKedaton Bandar Lampung which amounted to 54,569 KPP Tanjung Karang and amounted to 36,574at KPP Kedaton Bandar Lampung. he sample used in this research is determined by slovin method.Based on the motode, the number of samples of 100 taxpayers of e-Filing users is obtained.. Dataanalysis used in this research using Smart Partial Least Square (PLS).The result of the research shows that (1) there is a very significant positive influence on the perceptionof the use of e-Filing, (2) there is a very significant positive influence of perception of ease of e-filing,(3) there is a significant negative effect of security and confidentiality to e -Filing, (4) there is apositive influence of satisfaction perceptions on the use of e-Filing, (5) there is a positive effect ofinformation technology readiness on the use of e-Filing.